Student perceptions of the socialization and implementation Merdeka Belajar Kampus Merdeka program - Tridelvy Sensony; Dadang Sukirman; Ahmad Fajar Fadlillah (Curricula: Journal of Curriculum Development, 2024)
This study analyzes the perceptions of students of the Universitas Pendidikan Indonesia about the implementation of the Merdeka Belajar Kampus Merdeka Program Policy, including their interests and expectations related to learning activities. The background of this study focuses on the importance of socialization programs in improving student understanding and participation. The method used in this research is a quantitative approach with a descriptive design involving 40 respondents who are active students and have finished the program for at least one semester. Data were collected using a closed questionnaire with 30 statements with a Likert scale and then analyzed using descriptive analysis. The findings revealed that students' perceptions of program socialization and independent study implementation were rated to be in the category of "positive". This means that most of the respondents agreed that through socialization they became informed about the existence of the program and joined the same. Additionally, interests in learning were categorized as "very positive". These findings emphasize the importance of effective socialization in educational programs and can be a reference for developing better MBKM programs in the future. It is expected that this research will contribute to an increase in the quality of education in Indonesia.   Abstrak Penelitian ini menganalisis persepsi mahasiswa Universitas Pendidikan Indonesia tentang implementasi Kebijakan Merdeka Belajar Kampus Merdeka, termasuk minat dan harapan mereka terkait dengan kegiatan pembelajaran. Latar belakang penelitian ini berfokus pada pentingnya program sosialisasi dalam meningkatkan pemahaman dan partisipasi mahasiswa. Metode yang digunakan dalam penelitian ini adalah pendekatan kuantitatif dengan desain deskriptif yang melibatkan 40 responden yang merupakan mahasiswa aktif dan telah menyelesaikan program minimal satu semester. Data dikumpulkan menggunakan kuesioner tertutup dengan 30 pernyataan dengan skala likert kemudian dianalisis menggunakan analisis deskriptif. Hasil penelitian menunjukkan bahwa persepsi mahasiswa terhadap sosialisasi program dan implementasi studi mandiri dinilai dalam kategori "positif". Artinya sebagian besar responden setuju bahwa melalui sosialisasi mereka menjadi tahu tentang keberadaan program dan mengikutinya. Selain itu, minat belajar dikategorikan "sangat positif". Temuan ini menekankan tentang pentingnya sosialisasi yang efektif dalam program pendidikan dan dapat menjadi acuan untuk mengembangkan program MBKM yang lebih baik di masa mendatang. Diharapkan penelitian ini akan memberikan kontribusi bagi peningkatan kualitas pendidikan di Indonesia. Kata Kunci: kampus merdeka; minat belajar; persepsi mahasiswa